Situation and tasks of Hungarian national economy. Resolution adopted at the session of the central committee of the Hungarian Working People's Party (October 1-3, 1954) (Athenaeum printing office, 1954)
Repr.: "Szabad Nép", October 22, 1954. Supplement to "Hungarian bulletin", no 177, November 5, 1954.